Pengaruh Persepsi Pengalaman Auditor Dan Independensi Auditor Terhadap Kualitas Audit (Studi Kasus Mahasiswa Akuntansi Di Unviersitas Surakarta) - ., Sarsiti (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2013)
Audit quality is significant to result statement report, can believe in people. This is particulary needed in the presentation of the financial statements, because of concerns yhe public perception. The purpose of te research was to determine the influence ofÂ  perception of the auditorâs experience, the perception of the independence of the Auditors of the quality audit. The hypothesis of this research âis thought to have influenced the perception of the independence of the auditor, auditor experience of the quality auditâ. The object of the research was the accounting students grade VII at University of Surakarta. A population study of 44 respondents, for a population of less than 100, so all made sample (census). The collection of data using questionnaire (inquiry).Â Â  Analysis of the research use double linear regretion. The t test analysis result can be known that p-value (0.001<0.05), so Ho rejected and accepted Ha, does that mean there are influences the perception of the independences of the auditor, auditor experience of the quality audit. Based on the coefficient of determination, then it can be noted that the adjusted R Square (R2) value in the study of 0.684. So that, it can be interpreted that the variations independent variable consisting of the perception of the auditorâs experience(X1) and perception of the independence of the Auditors has contributed to the quality of audits(Y) of 68.4% while the rest amounted to 31.6% is influenced by other factors, such as moral education of Auditors.Keywords: experience the auditor, auditor independence, quality auditor